An evaluation of the factors affecting consumer resistance to innovation diffusion of e-cigarettes among South African university students - Johnson, Nastasje (My University, 2016)
With an increase in the concern over the harmful effects of smoking traditional tobacco cigarettes, there has been an increase in the use of a smoking alternative considered to be a healthier option, namely the e-cigarette. Thus, it is of interest to understand certain factors surrounding the novelty, and this research has been conducted in terms of evaluating the predictors of the diffusion of innovations on consumer resistance towards the e-cigarette among South African university students, with the primary purpose being to research a gap in the South African e-cigarette market, and to utilise the results to better understand the overall market. The gap in prior research has been identified as what appears to be a lack of information regarding the South African e-cigarette market, and in particular, the predictors of consumer resistance, including relative advantage, compatibility, complexity, trialability, observability, and perceived risk. The study undertook a quantitative methodology in which 400 students from the University of the Witwatersrand were asked to complete a self-administered questionnaire. Data analysis was conducted using SPSS 22 and AMOS for structural equation modelling. The results indicate that three of the six hypotheses are supported. Thus, indicating that marketers should focus on applying relative advantage, complexity, and perceived risk to marketing strategies. This study contributes to existing literature and contextual knowledge regarding consumer resistance and the diffusion of innovation. The results further provide marketing practitioners with a better understanding on how to limit consumer resistance and how to improve product diffusion of the e-cigarette, subsequently improving the rate of adoption. However, future research is necessary for corroboration.
Submitted in full fulfilment of the requirements for the degree of MASTER OF COMMERCE (Marketing) at the UNIVERSITY OF THE WITWATERSRAND 2015
Keywords: College students--Tobacco use--South Africa; Electronic cigarettes; Smoking--South Africa--Public opinion; Tobacco industry--South Africa--Marketing; Diffusion of innovations